EFFECT OF PHYTO-HORMONES 2,4-D AND KINITIN, APPLICATIONS ON ALKALOIDS ACCUMULATION IN Hyoscyamus albus L. (Sciences & Technologie. C, Biotechnologies, 2007)
Hyoscyamus albus L. is a medicinal plant pertaining to Solanaceae familly, it is rich mainly in tropanic  alkaloids  such  as  atropine  and  scopolamine.  Plants  of  this  specie  were  grown  under controlled conditions, irrigated to half field capacity and treated with hormones,  kinهtin (K) and  2,4-dichlorophenoxyacetic acid (2,4-D), at 0, 10 and 20 mg/l rates to follow the kinetic of alkaloids accumulation in the aerial and root parts. The results showed that spreading hormones increased alkaloids accumulation by a threefold  rate estimated to be 1.98% in the aerial parts and by a fourfold rate estimated to be 1.55% in the root parts. The checks accumulated 0.73% and 0.38% for the two hormones cited in that order. A synergetic effect was observed between both hormones at higher applied rates (20 mg/l) on the measured traits and accumulated alkaloids compared to their separated effect. Hyoscyamus albus L. contains 5 alkaloids in the aerial and 6 the root parts. Ethanol was foundto be the best solvent for the extraction of theses alkaloids.